1985
DOI: 10.1017/s0043174500082187
|View full text |Cite
|
Sign up to set email alerts
|

Control of Velvetleaf (Abutilon theophrasti) and Common Cocklebur (Xanthium pensylvanicum) in Soybeans (Glycine max) with Sequential Applications of Mefluidide and Acifluorfen

Abstract: Single and sequential applications of mefluidide {N-[2,4-dimethyl-5-[[(trifluoromethyl)sulfonyl] amino] phenyl] acetamide} and acifluorfen {5-[2-chloro-4-(trifluoromethyl)phenoxy]-2-nitrobenzoic acid} were evaluated in the field for velvetleaf (Abutilon theophrastiMedic. ♯ ABUTH) and common cocklebur (Xanthium pensylvanicumWallr. ♯ XANPE) control in soybeans [Glycine max(L.) Merr. ‘Williams’]. Acifluorfen was applied at 0.4 or 0.6 kg ai/ha alone or 3, 5, or 7 days following application of 0.1 or 0.3 kg ai/ha m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Most studies indicate that POST herbicides are most effective on smaller weeds (7,8,10). Controlling larger weeds normally requires higher herbicide rates, which may reduce effectiveness (12).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies indicate that POST herbicides are most effective on smaller weeds (7,8,10). Controlling larger weeds normally requires higher herbicide rates, which may reduce effectiveness (12).…”
Section: Introductionmentioning
confidence: 99%
“…As postemergence herbicides were developed, researchers observed more effective weed control when herbicides were applied to earlier growth stages at a given rate (1,7,8,11,12). Higher herbicide rates and sequential applications were often required to control weeds at later growth stages (14,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The use of postemergence herbicides for grass and broadleaf weed control, without preemergence herbicides, has also been investigated (3,8,9). However, antagonism caused by tank-mixing postemergence grass and broadleaf herbicides can reduce efficacy and require the use of higher herbicide rates (3,4,5,11).…”
Section: Introductionmentioning
confidence: 99%
“…The use of addi tives increased the control of velvetleaf and prickly sida in 1985, but there was no difference between petroleum oil concentrate and mefluidide as en hancing agents. Glenn et al (3) reported that adding mefluidide to acifluorfen often enhanced the con trol of velvetleaf and common cocklebur. How ever, they did not evaluate an oil-base additive.…”
Section: Volume 1 Issue 2 (April) 1987mentioning
confidence: 99%
“…McWhorter and Barrentine (5) noted that sequential applications of mefluidide plus dinoseb or 2,4-DB enhanced common cocklebur control. Glenn et al (3) noted that sequential appli cations of mefluidide plus acifluorfen allowed greater flexibility in the timing of application without reducing the control of velvetleaf or common cockle bur.…”
Section: Volume 1 Issue 2 (April) 1987mentioning
confidence: 99%